DAMPAK PEMBANGUNAN PERUMAHAN TERHADAP KONDISI SOSIAL EKONOMI PETANI DI NAGARI SALIDO KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Mulya, Ressa; Rahmadani, Sri; Wijaya, Wibi (Universitas Tanjungpura, 2022)
Agricultural land is now starting to be converted for development because agricultural land can be purchased at affordable prices and then the land is conditioned to be used as development land. The shift in the function of agricultural land will certainly have an impact on people's lives in the future, both from a social and economic perspective. The purpose of the study was to describe the impact of housing development on the socio-economic conditions of farmers in Nagari Salido, District IV Jurai, Pesisir Selatan Regency. The theory used in this research is the Structural Functional theory proposed by Robert K Merton. The research was conducted in Nagari Salido, District IV Jurai, Pesisir Selatan Regency. This research uses qualitative research method with descriptive research type. Withdrawal of informants is done by purposive sampling technique. The method of data collection in this study began with observation, in-depth interviews, and document studies. Data analysis techniques in research can be carried out in several stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that there were several impacts of housing development on the social and economic conditions of the community, including: 1) Farmers lost their jobs. 2) Lack of interaction between immigrant communities and local communities, and 3) Opening new job opportunities for the surrounding community